Alzheimer-Like β-Amyloid plaques in the brain of an aged stenella - Favole, Alessandra; Testori, Camilla; Mattioda, Virginia; Gallo, Marina; Grattarola, Carla; Orekhova, Ksenia; Avanzato, Tiziana; Iulini, Barbara; Fernández Rodríguez, Antonio Jesús; Alonso Almorox, Paula; Sacchini, Simona; Garibaldi, Fulvio; et al. (2024)
The main reason Alzheimer's disease (AD) is thought to be a human illness is the lack of reliable animal models for spontaneous disease. The complexity and comparability of the brain, along with age-related problems, present challenges for experimental animal models. Recently, Amyloid-β (Aβ) plaques (APs) and phosphorylated tau (ptau) changes in neurons and neuropil were observed in different mammal species, with very few descriptions in cetaceans, which have an Aβ aminoacidic sequence similar to that of humans. This study describes Aβ deposition in the brain tissue of a female striped dolphin (Stenella coeruleoalba) stranded in the Ligurian coast of the Pelagos Sanctuary in 2015 (DCC 2). The 18-year-old dolphin, submitted for complete postmortem investigations, in the brain presented a moderate pyogranulomatous encephalitis, with diffuse gliosis and multiple nodules of microglia. Four different areas of cerebral and cerebellar cortex, considered target areas for AD pathology according to the “ABC” criteria defined by the National Institute on Aging and Alzheimer’s Association, underwent immunohistochemical analysis. The immunolocalization of Aβ was tested using a rabbit monoclonal antibody (Ab) [mOC64] (ab201060, Abcam), while pTau was detected through 2 Abs: AT180 (MN1040, ThermoFisher) and AT8 (MN1020, ThermoFisher). Brain tissues from (1) human patients with AD and/or only APs and (2) an Atlantic spotted dolphin (S. frontalis) stranded in the Canary Islands (Sacchini et al., 2020), served as positive control sections. Extracellular and intracellular Aβ deposition, forming APs, was observed in the frontal cortex, while labelling of pTau tested through AT8 Ab, was present in the parietal cortex of the studied animal. No labelling was detected by AT180 Ab.Our initial results support the hypothesis that cetaceans, in particular toothed whales, might spontaneously exhibit AD-like pathology, possibly serving as unique natural models for AD. However, assessing clinical signs essential for an AD diagnosis proves ...